A formação do catequista a partir do Documento Catequese Renovada - Pereira, Geraldo Raimundo (2014)
This dissertation deals with the importance of the catechist and his training for the life of the Church, following the indications of the Documento Catequese Renovada. The formation of the catechist is presented as one of the great challenges facing the Church. Despite the big changes in society, in the world today, we can no longer catechise without a proper training. The Word of God stands, but must be presented in a new and more meaningful for the contemporary human way. The Documento Catequese Renovada was an advance renewed catechesis catechetical act in the Church in Brazil. Other magisterial documents affirm the importance of training of catechists for the mission. In this study, we focus on the importance of biblical, doctrinal, spiritual, ecclesial and social formation of catechists, emphasizing his spiritual life